Trading activity and stock price volatility: intraday and day of the week effects. - Ariva. (2008)
The purpose of this research is to establish the relationship between stock price volatility with volume, frequency, average trade size, dollar volume, and market return. This paper utilized SPSS software to determine if the independent variables have an impact on the volatility of stock price.